Thermal inkjet makes label-free single-cell proteomics accessible and easy - Stanisheuski, Stanislau; Ebrahimi, Arpa; Vaidya, Kavi Aashish; Jang, Hyo Sang; Yang, Liping; Eddins, Alex Jordan; Marean-Reardon, Carrie; Franco, Maria Clara; Maier, Claudia Susanne (Frontiers in Chemistry, 2024)
In this study, we adapted an HP D100 Single Cell Dispensera novel low-cost thermal inkjet (TIJ) platform with impedance-based single cell detectionfor dispensing of individual cells and one-pot sample preparation. We repeatedly achieved label-free identification of up to 1300 proteins from a single cell in a single run using an Orbitrap Fusion Lumos Mass Spectrometer coupled to either an Acquity UPLC M-class system or a Vanquish Neo UHPLC system. The developed sample processing workflow is highly reproducible, robust, and applicable to standardized 384-and 1536-well microplates, as well as glass LC vials. We demonstrate the applicability of the method for proteomics of single cells from multiple cell lines, mixed cell suspensions, and glioblastoma tumor spheroids. As additional proof of robustness, we monitored the results of genetic manipulations and the expression of engineered proteins in individual cells. Our cost-effective and robust single-cell proteomics workflow can be transferred to other labs interested in studying cells at the individual cell level.